Rancang Bangun Sistem Pengolah Air Bersih Standar WHO dan Kemenkes Bagi Warga Dusun Sinan - Desa Gawerejo - Kecamatan Karangbinangun - Kabupaten Lamongan Jawa Timur - Purwadi Agus Darwito; Halimatus Sa’diyah; Murry Raditya (Pengabdian dan Pengembangan Masyarakat Sekolah Vokasi UGM, 2019)
Sinan Village is located in Karangbinangun Subdistrict, Lamongan city, which is experiencing a shortage of clean water. The main source of water for the people in that village is originated from river water of Bengawan Solo branches which is mixed with pond water and is collected in a pond. The results of the pH, turbidity and TDS tests that have been carried out show that the Bengawan Solo water does not meet WHO's clean water standards and the standard from Ministry of Health. In this study, the design of the river and pond water filtration control system in the reservoir was carried out. The designed filtration system consists of the deposition stage and filtering stage. Deposition stage is carried out by using alum as a purifying medium and aims to simplify the screening phase. While the screening stage is carried out using stone, sand, charcoal and palm fiber which aims to increase the pH value and reduce the value of turbidity and TDS. The system is designed in a modular manner between each filtration stage to fascillitate the maintenance process of the system and flushing the remaining deposits produced by the filtration process. Testing result of this system is done by varying the variables of volume and height of sand used and it is known that the difference in sand volume used has a significant effect on the levels of TDS, Turbidity, and pH of the resulting clean water.